Knowledge spillovers and workers’ absorptive capacity in manufacturing industry - Ahmad Mustakim Mohamad,; Norhanishah Mohamad Yunus, (Penerbit Universiti Kebangsaan Malaysia, 2024)
This article examines the relationship between FDI and workers’ absorptive capacity on knowledge spillovers by constructing an augmented human capital model based on their education and job training experience. Employing a quantile regression estimator, the model scrutinises the knowledge flow from multinational corporations (MNCs) via labour mobility spillovers. This study use Malaysian manufacturing industry data from 2000 to 2019. The results of the study revealed that the Malaysian manufacturing industry has the potential to receive more than 30% of knowledge spillovers from FDI if the level of absorptive capacity of degree and diploma-educated workers reaches the highest quantile. The locally trained workers’ absorptive capacity to exploit the foreign knowledge spillovers transferred from skilled workers who have worked in MNCs is assimilated only at the 25th quantile of the conditional knowledge spillovers of FDI distributions. This study suggests creating a lucrative reward system for those who successfully transfer the technological knowledge learned while working in multinational companies to employees in local firms. In addition, large-scale training institutions with comprehensive training programs need to be established at all levels of education, especially for the younger generation.